Краківська доба життя та діяльності Степана Томашівського у світлі документів Архіву Яґеллонського університету - Тельвак, В. (Архіви України, 2009)
The article is devoted to the documents of Jagiellonian University‘s archive. The circumstances of researcher‘s defense of doctoral work have been found out, University has been researched. In the addition to the article the comment translation of the historian‘s autobiography of 1930 year has been published.